PERUBAHAN NON-FORMAL KONSTITUSI DI INDONESIA PASCA-REFORMASI BERDASARKAN PEMIKIRAN FAJRUL FALAAKH - Aldiansyah, Aldiansyah (AL WASATH Jurnal Ilmu Hukum, 2021)
The constituent changes in Post-Reformation Indonesia are very interesting to discuss ranging from formal amendment changes and non-formal changes that change without changing the text of the constitution in question. Also happens informally (informal change informal amendment), namely changes to the contituents without changing the text of the contitution concerned or changes outside the text of the contitutionâ€. Formal amendments (formal changes) are only one way to change the constitution. Changes can also occur non-formally (informal changes, informal amendments), namely changes to the constitution without changing the text in question or changes "outside the text of the constitution" (buiten de grodwet). Constitutional norms can change when further regulated in law by the legislature, or determined by a judge to determine the law of a case he is trying. Fajrul Falaakh contributed research results in his book "Growth and Constitutional Models", to describe the occurrence of non-formal changes to the constitution in the normative realm as well as in an empirical perspective, so as to obtain wider benefits. The lack of synchronization in the constitutional legal system or regime certainly has an impact on the constitutional system based on the 1945 Constitution of the Republic of Indonesia, especially on the fields contained in the constitution that undergo non-formal changes. From the review of the results of FF's research, it was identified that it would be useful as a legislative review by legislators, judicial review by the Constitutional Court, changes in the behavior of the political elite and society to the politics of changing the constitution.